Aberrant expansion of follicular helper T cell subsets in patients with systemic lupus erythematosus - Jin, Xin; Chen, Jia; Wu, Jian; Lu, Ying; Li, Baohua; Fu, Wenning; Wang, Wei; Cui, Dawei (Frontiers in Immunology, 2022)
Objective Systemic lupus erythematosus (SLE) is a chronic and complex autoimmune disease characterized by multiple autoantibodies, resulting in multiple organ and tissue damages. These pathogenic autoantibodies produced by B cells are closely correlated with follicular helper T (Tfh) cell subsets that play a fundamental role in the pathogenesis of SLE. The aim of the present study was to study the phenotype and role of circulating Tfh (cTfh) cell subsets and associated B cell subpopulations in active and inactive SLE patients. Methods Thirty SLE outpatients and 24 healthy controls (HCs) were enrolled in this study. The frequency of cTfh cell and B cell subsets in peripheral blood mononuclear cells (PBMCs) and the plasma levels of eight cytokines were determined by flow cytometry, and plasma IL-21 levels were measured by ELISA. Meanwhile, we used MRL/lpr mice as the model of SLE to research the alterations of Tfh cells in the thymus and spleen of mice. Results Frequencies of CD4+CXCR5+CD45RA-effector cTfh cells, PD1+cTfh, PD1+ICOS+cTfh, PD1+cTfh1, PD1+cTfh2, PD1+cTfh17, and PD1+ICOS+cTfh1 cells as well as plasmablasts showed significant differences among HC, active and inactive SLE patients. Moreover, cytokines typically associated with cTfh cells, including IL-6 and IL-21, were elevated in active SLE patients compared to inactive SLE patients and HCs. Additionally, a positive correlation was observed between PD1+ICOS+ cTfh or PD1+ICOS+ cTfh1 cell frequencies and plasmablasts or IL-21 levels, as well as between plasmablasts. We also found PD1+ICOS+ Tfh cells expansion in both thymus and spleen of MRL/lpr mice, accompanied by increased frequencies in B cells and plasmablasts, meanwhile, cTfh1which expressing IFN-γ was increased in the peripheral blood of MRL/lpr mice. Conclusion Tfh cell subsets and plasmablasts may play a fundamental role in the pathogenesis of SLE and may provide potential targets for therapeutic interventions for SLE.